2022
DOI: 10.3389/fimmu.2022.865245
|View full text |Cite
|
Sign up to set email alerts
|

Emerging innovations on exosome-based onco-therapeutics

Abstract: Exosomes, nano-sized extracellular vesicles for intercellular communications, are gaining rapid momentum as a novel strategy for the diagnosis and therapeutics of a spectrum of diseases including cancers. Secreted by various cell sources, exosomes pertain numerous functionalities from their parental cells and have enhanced stability that enable them with many features favorable for clinical use and commercialization. This paper focuses on the possible roles of exosomes in cancer therapeutics and reviews curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 181 publications
0
14
0
Order By: Relevance
“…Exosomes have natural stability, low immunogenicity and excellent tissue/cell penetration ( 22 ), and is expected to become an advanced platform for drug/gene delivery ( 12 ). Owing to their unique properties, exosomes are currently under evaluation as vehicles for the transport of tumor therapeutic drugs ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Exosomes have natural stability, low immunogenicity and excellent tissue/cell penetration ( 22 ), and is expected to become an advanced platform for drug/gene delivery ( 12 ). Owing to their unique properties, exosomes are currently under evaluation as vehicles for the transport of tumor therapeutic drugs ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes have natural stability, low immunogenicity and excellent tissue/cell penetration ( 22 ), and is expected to become an advanced platform for drug/gene delivery ( 12 ). Owing to their unique properties, exosomes are currently under evaluation as vehicles for the transport of tumor therapeutic drugs ( 12 ). For example, intravenous administration of MSCs is often retained in the lung or liver, while MSC-exo can avoid this problem while still maintaining the therapeutic function of their originating cells ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Being released from almost all cell types and playing a dynamic role in intercellular communication, exosomes have recently been extensively investigated as novel immunotherapeutic agents with the ability to regulate various immune responses (Kugeratski and Kalluri, 2021;Dai et al, 2022;Dutta and Paul, 2022). Research has revealed that exosomes exhibit immunoregulatory or immunostimulatory effects through different pathways (Olejarz et al, 2020;Benjamin-Davalos et al, 2021;Kugeratski and Kalluri, 2021).…”
Section: Exosomes' Immunomodulation Properties and Immunotherapeutic ...mentioning
confidence: 99%